Cognitive mechanisms of episodic simulation in psychiatric populations. (January 2021) - Brunette, Amanda M.; Schacter, Daniel L.
Abstract: Episodic simulation is the construction of a mental representation of a specific autobiographical future event. Episodic simulation has increasingly been studied in psychiatric populations. Here we 1) review evidence indicating that episodic simulation is compromised in patients with depression, anxiety, schizophrenia, bipolar disorder, and PTSD; and 2) consider several potential cognitive mechanisms of episodic simulation in psychiatric populations: episodic retrieval, scene construction, mental imagery, components of the CaRFAX model (i.e., capture and rumination, functional avoidance, and executive functioning), and narrative style. We evaluate evidence regarding these mechanisms across psychiatric populations, and identify areas of future research. Understanding the factors that contribute to episodic simulation impairment in psychiatric populations may lead to targeted and effective treatment approaches. Highlights: Episodic simulation is the ability to imagine a specific future event. Psychiatric populations have difficulty simulating specific events in the future. Impairments to specific cognitive processes may impact episodic simulation in psychiatric conditions.